Acute Stress Enhances Epigenetic Modifications But Does Not Affect the Constitutive Binding of pCREB to Immediate-Early Gene Promoters in the Rat Hippocampus - Carter, Sylvia D.; Mifsud, Karen R.; Reul, Johannes M. H. M. (Frontiers in Molecular Neuroscience, 2017)
The immediate early genes c-Fos and Egr-1 are rapidly and transiently induced in sparse neurons within the hippocampus after exposure to an acute stressor. The induction of these genes is a critical part of the molecular mechanisms underlying successful behavioural adaptation to stress. Our previous work has shown that transcriptional activation of c-Fos and Egr-1 in the hippocampus requires formation of a dual histone mark within their promoter regions, the phosphorylation of serine 10 and acetylation of lysine 9/14 of histone H3. In the present study, using chromatin immuno-precipitation (ChIP), we found that an increase in the formation of H3K9ac-S10p occurs within the c-Fos and Egr-1 promoters after forced swim stress in vivo and that these histone modifications were located to promotor regions containing cAMP Responsive Elements (CREs), but not in neighbouring regions containing only Serum Responsive Elements (SREs). Surprisingly, however, subsequent ChIP analyses showed no changes in the binding of pCREB or CREB-binding protein (CBP) to the CREs after forced swimming. In fact, pCREB binding to the c-Fos and Egr-1 promoters was already highly enriched under baseline conditions and did not increase further after stress. We suggest that constitutive pCREB binding may keep c-Fos and Egr-1 in a poised state for activation. Possibly, the formation of H3K9ac-S10p in the vicinity of CRE sites may participate in unblocking transcriptional elongation through recruitment of additional epigenetic factors.